Authoritative Parenting and Self-Efficacy as Predictitors of Junior High School's Academic Achievement during The Covid-19 Pandemic - Azzala, Quineke Laksmi; Arjanggi, Ruseno (Universitas Trunojoyo Madura, 2022)
This research aimed to determine the relationship between authoritative parenting style and self-efficacy with student mathematics learning achievement in Junior High School X Tegal. This research used quantitative methods. The subjects in this research were 330 Junior High School X Tegal students for the 2021/2022 school year. The sampling technique was the cluster random sampling technique. This research used two scales and a report on students' mathematic learning achievement. The authoritative parenting style's first scale consists of 17 items with a score of a reliability coefficient of 0,781. The second scale is the self-efficacy scale consists of 17 items with a score of a reliability coefficient of 0,749. This research used analysis regression and partial correlation technique for analyzing the data. The first hypothesis's result showed no relationship between authoritative parenting style and self-efficacy with students mathematics learning achievement, R equal with 0,073, F equal with 0,864, and p equal with 0,422 (p more than 0,05), which means the hypothesis is not accepted. The second hypothesis showed that authoritative parenting style and students' mathematics learning achievement have no correlation, r1-2 equal with 0,073, p equal with 0,190 (p more than 0,05), which means the hypothesis is not accepted. The third hypothesis showed that self-efficacy and students' mathematics learning achievement have no correlation, r2-1 equal with -0,021 and p equal with 0,703 (p more than0,05), which means the hypothesis is not accepted.